Meningkatkan Hasil Belajar Dan Bernalar Kritis Pakbp Melalui Model PBL Berbantuan Wayang Kardus Fase B Kelas IV - Kurniatisari Kurniatisari; FR. Wuriningsih; Budi Hartana (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Nowadays, Critical Thinking plays a significant role and totally needed because it is closely related to the improvement of Profile Pelajar Pancasila as one of the Indonesian educational goals. It helps students to understand and prefer to be a selective person in giving and taking information, and it also makes the students become wiser in taking a decision based on Pancasila values. In fact, it is still found that there are many elementary school students' critical thinking abilities are still low. The purpose in doing this research is in order to know the effect of the Problem Based Learning (PBL) method to assisted cardboard puppet learning media on the result of learning and critical thinking skills in the subject of Catholic Religious Education and Character (PAKBP) about